A simple system for phenotyping of plant transpiration and stomatal conductance response to drought. (April 2023) - Driever, Steven M.; Mossink, Leon; Ocaña, Diego Nuñez; Kaiser, Elias
Abstract: Plant breeding for increased crop water use efficiency or drought stress resistance requires methods to quickly assess the transpiration rate ( E ) and stomatal conductance ( g s ) of a large number of individual plants. Several methods to measure E and g s exist, each of which has its own advantages and shortcomings. To add to this toolbox, we developed a method that uses whole-plant thermal imaging in a controlled environment, where aerial humidity is changed rapidly to induce changes in E that are reflected in changes in leaf temperature. This approach is based on a simplified energy balance equation, without the need for a reference material or complicated calculations. To test this concept, we built a double-sided, perforated, open-top plexiglass chamber that was supplied with air at a high flow rate (35 L min −1 ) and whose relative humidity (RH) could be switched rapidly. Measurements included air and leaf temperature as well as RH. Using several well-watered and drought stressed genotypes of Arabidopsis thaliana that were exposed to multiple cycles in RH (30–50 % and back), we showed that leaf temperature as measured in our system correlated well with E and g s measured in a commercial gas exchange system. Our results demonstrate that, at least within a given species, the differences in leaf temperature under several RH can be used as a proxy for E and g s . Given that this method is fairly quick, noninvasive and remote, we envision that it could be upscaled for work within rapid plant phenotyping systems. Highlights: A simple system for phenotyping plant transpiration, built with off-the-shelf components, is presented. Rapid switches between low and high air humidity cause changes in leaf temperature, which correlate with transpiration rate. The method is validated against an established method, namely photosynthetic gas exchange.